Agentes de contraste nanoestruturados a base de óxido de ferro : síntese, caracterização e avaliação toxicológica - Oliveira, Elisa Magno Nunes de (2018)
The present study focuses on the development of nanoparticles with an iron oxide magnetic core, with different biocompatible coatings, and on a comparative study of their toxicities. Uncoated and dextran-, chitosan-, polyethylene glycol- and silica-coated nanoparticles were synthesized. The addition of optical markers of the benzo-thiazoles class was also accomplished. The physico-chemical properties of the nano-particles were characterized, including their magnetic, optical and contrast properties in nuclear magnetic resonance imaging (relaxivities). In the particular case of nanopar-ticles functionalized with 6-OH-BTA-1 molecules, the affinity to the beta-amyloid pep-tide was also investigated. A second step was to evaluate the toxicological effects of these nanoparticles in vitro (using in VERO cells), and in vivo with zebrafish as an animal model. The size of the nanoparticles with the coatings ranged from 13 to 30 nm. Their crystalline structure was consistent with the ferrite spinel. The nanoparticles, independent of the coating, did not present residual magnetization and hysteresis, in-dicating superparamagnetic behaviour. For most nanoparticles, the r2 transverse re-laxivity values ranged from 76-64 mM-1.s-1, exceptfor uncoated and chitosan-coated nanoparticles, which present higher values, possibly due to the aggregation. The val-ues of r1 were similar for all nanoparticles (12.6 to 18 mM-1.s-1), with the exception of silica-coated nanoparticles (r1=2.1 mM-1.s-1). The r2/r1 ratios were between 4 and 17, typical of commercially available negative contrast-agents. The nanoparticles function-alized with benzothiazoles showed fluorescence with a Stokes shift of the emission peak of ~ 197 nm. The interaction of the beta-amyloid peptide with the 6-OH-BTA-1 molecule analyzed by fluorescence suppression is characterized by a static mecha-nism and Stern-Volmer constants of 1.53x104 mM-1 for the monomeric form, 1.40x104 mM -1 for oligomers) and 1.33x104 mM -1 for amyloid plaques.The in vitro toxicity assays indicated acceptable values of cell viability for iron concentration up to 2 mmol.L-1. The nanoparticles with the carboxysilane and polyethylene glycol showed higher biocom-patibility and silica-coated nanoparticles had the highest cytotoxicity. The in vivo as-says did not show significant changes in survival and hatchability rates, except for doses greater than 2 mmol.L-1 in the case of the chitosan-coated nanoparticles. The percentages of animals with anatomical alterations were similar between the treated and control groups. In the locomotion and exploration tests, only chitosan- and silica-coated nanoparticles induced significant changes.